Ramsay Hunt syndrome and mandibular alveolar bone necrosis following herpes zoster: A case report and literature review - Yin, Maojia; Huang, Panchuan; Yang, Sen; Wang, Wuchao (Frontiers in Neurology, 2022)
Background: Reactivation of latent varicella-zoster virus (VZV) can induce herpes zoster (HZ). Ramsay Hunt syndrome occurs through the reactivation and proliferation of VZV in the geniculate ganglion, which can lead to vesicular rash in the ear or oral mucosa, accompanied by neurological disorders. Materials and methods: A 50-year-old man sought remedy for pain of the right ear and face. Within 1 week, all his lower right teeth fell out and in the following 3 months, his lower right mandibular alveolar bone gradually became necrotic. In the past 20 days, he experienced blister rash, hearing and taste loss, and slight facial paralysis. Results: After ruling out tumors and other infectious diseases, he was diagnosed with trigeminal HZ and RHS. Conclusion: RHS with tooth loss and alveolar osteonecrosis is rare. It requires long-term treatment of pain, and prevention and treatment of tooth loss and alveolar bone necrosis are difficult and warrant further study.